2020
DOI: 10.1371/journal.pone.0227624
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive effect of anesthetics on the effect of limb remote ischemic postconditioning following ischemic stroke

Abstract: Limb remote ischemic postconditioning (LRIP) has been reported as an effective method to reduce the induced experimental stroke damage after ischemic reperfusion (IR) injury. Studies suggest that anesthetics used during induction of ischemic stroke can reduce IR injury, which could affect the actual mechanisms of neuroprotection by LRIP. This study focuses on the comparative effects of anesthetics such as isoflurane and ketamine-xylazine on ischemic injury when used during LRIP. Adult C57BL/6 mice were anesthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 44 publications
0
36
0
Order By: Relevance
“…Anesthetics were used during MCAO in all studies; most used chloral hydrate, 17–21,25–28 eight used isoflurane, 1,3,10,11,22–24,30 and two used the structural isomer enflurane 2,29 . One study used isoflurane and halothane during the MCAO to determine if either had additional effects on the outcomes of RIPostC 24 . Sodium pentobarbital was used prior to inducing RIPostC/sham procedures in two studies, but the type of anesthesia used was not reported 15,16 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Anesthetics were used during MCAO in all studies; most used chloral hydrate, 17–21,25–28 eight used isoflurane, 1,3,10,11,22–24,30 and two used the structural isomer enflurane 2,29 . One study used isoflurane and halothane during the MCAO to determine if either had additional effects on the outcomes of RIPostC 24 . Sodium pentobarbital was used prior to inducing RIPostC/sham procedures in two studies, but the type of anesthesia used was not reported 15,16 .…”
Section: Resultsmentioning
confidence: 99%
“…One study initiated RIPostC at 12 h, 24 h, and 5 days after MCAO, and applied it up to three times with variable time intervals to investigate very delayed post‐conditioning 23 . Two studies tested consecutive RIPostC; one initiated the protocol for 90 min and applied RIC for a total of four sessions during the following 72 h 24 and another initiated RIC at 48 h after reperfusion and applied it daily for 21 consecutive days 21 . In two studies testing the combination of RIPerC and RIPostC for 7 or 14 days, the RIPostC regime started 24 h after the MCAO 15,16 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations